Co-researching as a driver for technological innovation: Computing and Cultural Heritage - Arnold, David (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
A recurring question in defining publicly funded research programmes is “what research should be funded publicly and what should be funded through the private sector?”. The way this question is usually answered has placed emphasis on seeking to ensure that research that has a payback in purely economic terms is funded (at least in part) by those most likely to receive the economic benefit, but evaluating “who benefits?” and “how?” is not always easy to deduce from the research questions posed.